The Association of Length of the Resected Membranous Urethra With Urinary Incontinence After Radical Prostatectomy - Kohjimoto, Yasuo; Yamashita, Shimpei; Kikkawa, Kazuro; Iba, Akinori; Matsumura, Nagahide; Hara, Isao (Urology Journal, 2020)
Purpose: To retrospectively determine whether recovery of urinary continence after radical prostatectomy is associated with the preoperative length of membranous urethra (MU), the amount of rhabdosphincter and the length of MU removed with the prostate. Materials and Methods: The study cohort comprised 179 consecutive patients who underwent laparoscopic radical prostatectomy (LRP: n = 98) and robot-assisted radical prostatectomy (RARP: n = 81) at Wakayama Medical University between July 2010 and May 2014. The length of MU was measured by preoperative MRI. The amount of resected rhabdosphincter and the length of resected MU were assessed in hematoxylin and eosin sections at the apical margin of prostate specimens. Patient-reported urinary continence status was determined at 3, 6, 12 and 24 months postoperatively, with urinary continence considered as 0-1 pads/day. Kaplan-Meier analysis and the log-rank test were used to compare time to urinary continence recovery. Multivariate Cox regression analyses were performed to determine the predictors of urinary continence. Results: RARP vs LRP (p = 0.02) and shorter length of resected MU (p = 0.01) showed significantly better postoperative continence recovery by log-rank test. Nerve-sparing, preoperative length of MU, and amount of resected rhabdosphincter did not significantly correlate with continence recovery. Only the length of resected MU was the independent factor for predicting postoperative urinary continence by multivariate Cox regression analysis (hazard ratio 0.84, p = 0.01). Conclusion: These results demonstrated that the length of resected MU measured by specimen was an independent predictor of urinary incontinence after radical prostatectomy. Care should be taken to preserve maximal length of MU for optimal continence outcomes.